2021
DOI: 10.3390/cancers13030369
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between PI3K/AKT and Estrogen Receptor Signaling in Breast Cancer

Abstract: Signaling from estrogen receptor alpha (ERα) and its ligand estradiol (E2) is critical for growth of ≈70% of breast cancers. Therefore, several drugs that inhibit ERα functions have been in clinical use for decades and new classes of anti-estrogens are continuously being developed. Although a significant number of ERα+ breast cancers respond to anti-estrogen therapy, ≈30% of these breast cancers recur, sometimes even after 20 years of initial diagnosis. Mechanism of resistance to anti-estrogens is one of the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 160 publications
2
33
0
Order By: Relevance
“…Based on these criteria, study quality was rated on a scale from one star, very poor, to 10 stars, high quality. Studies are rated as of high (7-10), medium (5)(6) or low quality (< 4). Two review authors (EH and FKH) completed quality assessment independently.…”
Section: Evaluating the Quality Of Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these criteria, study quality was rated on a scale from one star, very poor, to 10 stars, high quality. Studies are rated as of high (7-10), medium (5)(6) or low quality (< 4). Two review authors (EH and FKH) completed quality assessment independently.…”
Section: Evaluating the Quality Of Articlesmentioning
confidence: 99%
“…In numerous studies, postmenopausal women who used estrogen had higher risk of breast cancer [ 4 , 5 ]. There are two subtypes of breast cancers: estrogen receptor-positive and estrogen receptor-negative [ 6 , 7 ]. About 70% of breast cancer cases express estrogen receptor alpha (ER) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of any association between NGB accumulation in breast cancer tissues and other estrogen receptors (e.g., ERβ and GPER) strongly sustains the results obtained in cancer cell lines confirming the pivotal involvement of the ERα/AKT pathway in NGB accumulation in breast cancer tissues. Although the literature on isoform-specific roles of AKT in cancer progression is still debated, the three functional AKTs encoded by distinct genes are all differently involved in cancer growth and progression (AKT1), survival (AKT1 and AKT3), as well as in metastasis, migration, and invasion (AKT2) [31]. In cancer cell lines, we demonstrated that membrane-bound Erα induces the rapid and persistent activation of PI3K-AKT [32], thus leading, among other effects, to the block of NGB degradation, the increase in NGB gene transcription via CREB, and NGB translocation to the mitochondria, which culminate in breast cancer survival against oxidative stress and the apoptosis prevention [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In HR+ breast cancer, both ER and PR are commonly co-expressed due, in part, to ER-dependent activation of PR expression [ 23 , 24 ]. These receptors play a prominent role in regulating cellular growth and tumor progression through activation of kinase signaling cascades and transcriptional regulation of signaling networks [ 25 , 26 , 27 , 28 , 29 , 30 ]. ER mediates effects on cellular signaling through ligand (estradiol)-induced activation of kinase signaling cascades resulting in aberrant PI3K/AKT/mTOR [ 25 , 26 , 31 ], Notch [ 27 , 28 , 32 , 33 , 34 ] and RAS/MAPK [ 29 , 30 , 35 , 36 ] signaling.…”
Section: Introductionmentioning
confidence: 99%
“…These receptors play a prominent role in regulating cellular growth and tumor progression through activation of kinase signaling cascades and transcriptional regulation of signaling networks [ 25 , 26 , 27 , 28 , 29 , 30 ]. ER mediates effects on cellular signaling through ligand (estradiol)-induced activation of kinase signaling cascades resulting in aberrant PI3K/AKT/mTOR [ 25 , 26 , 31 ], Notch [ 27 , 28 , 32 , 33 , 34 ] and RAS/MAPK [ 29 , 30 , 35 , 36 ] signaling. Following receptor internalization and nuclear translocation, ER functions as a transcription factor by binding to estrogen response elements (EREs) to mediate expression of genes that promote cell proliferation and survival [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%